An open trial of an anger management treatment in a correctional facility: preliminary effectiveness and predictors of response. Issue 5 (3rd September 2018) - McGonigal, Patrick T.; Dixon-Gordon, Katherine L.; Bernecker, Samantha L.; Constantino, Michael J.
ABSTRACT: Despite the prevalence of anger management programs in correctional settings, there is mixed support for their effectiveness, and little is known about who benefits most. This preliminary study aimed to (1) evaluate the effectiveness of anger management for inmates, and (2) examine baseline psychopathology and midtreatment variables as response predictors. Participants were 30 incarcerated men undergoing 12-session anger management groups. Post-intervention, inmate-reported anger, and disciplinary actions decreased. Increased reported emotion regulation strategies predicted anger reduction.